Hypogaeic anti epigaeic ant (Hymenoptera: Formicidae) assemblages of atlantic costal rainforest and dry mature and secondary amazon forest in Brazil: Continuums or communities - Fowler, H. G. [UNESP]; Delabie, J. H C [UNESP]; Moutinho, P. R S [UNESP] (My University, 2000)
Meat, flour and sugar baits were used on the soil surface and buried to examine species composition of the ant fauna in three separate tropical forests in Brazil, and to control for the effect of the regional faunal pool. Compositional mosaic diversities were comparable among areas, bait types and foraging strata. Mosaic diversity was independent of mean assemblage size. The number of unique species per sampling unit was correlated with mean assemblage size. Canonical correspondence analysis ordered species first by foraging substrate, second by geographic location, and third by diet. The first axis was significantly correlated with mean similarity and affinity. Mean Mahanalobis distances between centroids of groups based upon foraging strata were significantly larger than between localities, indicating local ecological pressures stronger than regional species pool constraints. As most. species foraged in only one stratum in one geographical position and were not omnivorous, the response of species to environmental gradients (continuums) showed a lower coherency with these patterns than did communities, structured around guilds based upon foraging strata and diet.
Keywords: Assemblages; Cannonical correspondence analysis; Foraging strata; Mosaic diversities; Regional species pool; ant; community composition; community structure; tropical forest; Brazil; Formicidae; Hymenoptera